ANALISIS PENGARUH CAREER ADAPTABILITY TERHADAP KOMPETENSI KARYAWAN DI PT BULISU PROPERTI CENDEKIA PADA MASA PANDEMI COVID-19 - Rindi Antika; Azwar Azwar; Erlyn Rosalina (Politeknik Negeri Jakarta, 2022)
The Covid-19 pandemic has occurred since 2020 which has had an impact on the Indonesian economy, one of which is the property business. Companies must implement a work from home to suppress the spread of the virus Covid-19. This makes many changes in work habits, so employees must be able to adapt well to support their competence. This study aims to determine the effect of career adaptability on employee competence at PT Bulisu Properti Cendekia during the pandemic and find out how big the influence of this. This study is a quatitative using a saturated sample involving 25 employees of PT Bulisu Properti Cendekia. This research was conducted by distributing questionnaires directly and via G-Form. The Instrument test carried out is the validity and reliability test. The data analysis technique used is simple linear regression analysis, simple correlation analysis (r), coefficient of determination (R2) and T-test using SPSS ver. 23. The results of simple regression analysis are Y = 26.271 + 1.241X. The result of this study indicate that career adaptability has a positive and significant effect on employee competence at PT Bulisu Properti Cendekia during the Covid-19 Pandemic by 32.1%.